14 Sex-specific predictors of coronary microvascular function in a multiethnic cohort of 455 asymptomatic people with type 2 diabetes. (28th January 2023) - Yeo, Jian L; Gulsin, Gaurav S; Dattani, Abhishek; Marsh, Anna-Marie; Brady, Emer M; Xue, Hui; Kellman, Peter; McCann, Gerry P
Abstract : Introduction: Type 2 diabetes (T2D) confers 10% higher relative risk of heart failure in women than men, 1 which may be linked to higher prevalence of coronary microvascular dysfunction. We aimed to determine the prevalence and sex-specific determinants of coronary microvascular dysfunction in asymptomatic people with T2D. Materials and Methods: We prospectively enrolled a multi-ethnic cohort of people with T2D and no evidence of cardiovascular disease and sex- and ethnicity-matched non-diabetic controls. Participants underwent echocardiography and stress perfusion cardiac MRI. Quantitative myocardial blood flow analysis was performed for measurement of myocardial perfusion reserve (MPR), an index of microvascular function. Multivariable linear regression was undertaken to identify the independent clinical and imaging predictors of MPR in people with T2D. Results: Excluding participants with silent myocardial infarction (n=7), we included 455 with T2D (42% women, age 57±11y, BMI 32±6 kg/m2 ) and 88 non-diabetic controls (43% women, age 52±12y, BMI 25±4 kg/m2 ). Women and men with T2D had increased LV concentricity, systolic, and diastolic dysfunction. MPR was significantly lower in T2D than controls (2.9±0.9 vs 3.5±1.1, p<0.001) and lower in diabetic women than men (2.7±0.9 vs 3.0±0.9, p<0.001). A greater proportion of women with T2D had MPR of <2.5 (45% vs 28%, p<0.001). In a regression model adjusting for clinical risk factors, only age (β=-0.184, p=0.004), female sex (β=-0.210, p<0.001) and systolic blood pressure (SBP) (β=-0.119, p=0.021) were independently associated with MPR in T2D. Sex- stratified analysis showed independent associations with MPR: age (β=- 0.221, p=0.022), SBP (β=-0.122, p=0.131), and BMI (β =-0.188, p=0.026) in women, and age (β=-0.150, p=0.085) and SBP (β=-0.155, p=0.027) in men. Imaging measures of LV concentricity, filling pressure, and diffuse fibrosis did not independently predict MPR in T2D. Discussion: In adults without cardiovascular disease, women who developed T2D had a greater reduction in MPR compared to men. This is associated with traditional risk factors but not subclinical cardiac remodelling. Early interventions focussed on blood pressure reduction and weight loss, may prevent coronary microvascular dysfunction. Conclusion: Age and systolic blood pressure are independent predictors of MPR in people with T2D. BMI is an additional independent risk factor for MPR in women but not men. Acknowledgements: Funding was provided by a NIHR research professorship award (RP2017–08-ST2–007), NIHR career development fellowship (CDF 2014–07- 045), a BHF Clinical Research Training Fellowship (FS/16/47/32190), the Medical Research Council (MRC) and Novo Nordisk. Reference: Ohkuma T, Komorita Y, Peters SAE, et al . Diabetes as a risk factor for heart failure in women and men: a systematic review and metaanalysis of 47 cohorts including 12 million individuals. Diabetologia 2019;62 :1550–1560.